(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The research deals with the absence or weakness the criteria in assessing the current sustainability indicators for residential neighborhoods, Which is the problem research, so the goal of the research to build a sustainability knowledge in the residential neighborhood with an attempt to measure sustainability indicators in six residential neighborhoods in the AL Kut city according to internationally approved criteria .The most important research results characterized the Anwar al-Sadr district as the best locality in response to the sustainability criteria that were adopted in the research board is the transport network efficiency, including the length of the road network ,area, , the residential density criterion, mixed use, the level of social integration and areas for specialized uses, That locality is less deviated from other stores than what is required to achieve those criterion and a total deviation of 43.2% is required for the criteria. Al-Imam Neighborhood was less sustainable, with a total deviation of 85.7% of the criteria to be achieved. The research emphasize to need for local research institutions specialized in Iraqi universities to re-evaluate the criteria adopted for sustainability, relying on international institutions such as the United Nations and other specialized organizations.